The Impact of Sustainable Balance Scorecard to Achieve Competitive Advantage in the Kurdistan Region of Iraq Economic Unit (Raparin Journal of Humanities (RJH), 2023)
The current research explores the important role of SBSC in initiating basic and important elements of competitive advantages in education sector economic units. Private universities and institutions in the current dynamic and complex environmental circumstances should consider SBSC as a unique tool and perceived to be good in the hands of managers to improve the abilities of their competitive advantage. A sample of (137) respondents has been analyzed by using statistical methods (SPSS 24), and principally measures of SBSC as independent variables represent the following perspectives: financial, customer, learning and growth, internal business, environmental and social as employed construct measures enhance effectiveness measures of competitive advantage components which represent in this study (cost, quality, time and innovation). Although, analysis of the study model test shows a statistically significant association of proposed SBSC perspectives on determinants of competitive advantage; hence result recommends reliance on SBSC orientation on private university and institution performance and competitive advantage.